2021
DOI: 10.1111/nmo.14251
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors for gastrointestinal symptoms after recovery from COVID‐19

Abstract: Background COVID‐19 frequently presents with acute gastrointestinal (GI) symptoms, but it is unclear how common these symptoms are after recovery. The purpose of this study was to estimate the prevalence and characteristics of GI symptoms after COVID‐19. Methods The medical records of patients hospitalized with COVID‐19 between March 1 and June 30, 2020, were reviewed for the presence of GI symptoms at primary care follow‐up 1 to 6 months later. The prevalence of new GI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
54
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(60 citation statements)
references
References 25 publications
(51 reference statements)
4
54
0
2
Order By: Relevance
“…However the wording of the question “Have you noticed the following symptoms or illnesses since your COVID-19 diagnosis ?” limits the risk of reporting symptoms not related to COVID-19. Moreover, the appearance of symptoms in asymptomatic patients or after recovery of the acute illness has been reported by other studies [ 41 , 45 ]. It can be questionable whether gastrointestinal symptoms could be associated with COVID-19 1 year after infection.…”
Section: Discussionsupporting
confidence: 58%
“…However the wording of the question “Have you noticed the following symptoms or illnesses since your COVID-19 diagnosis ?” limits the risk of reporting symptoms not related to COVID-19. Moreover, the appearance of symptoms in asymptomatic patients or after recovery of the acute illness has been reported by other studies [ 41 , 45 ]. It can be questionable whether gastrointestinal symptoms could be associated with COVID-19 1 year after infection.…”
Section: Discussionsupporting
confidence: 58%
“…Among 285 survivors, 40% reported new GI symptoms. 14 In a study from China on 1655 subjects, 80 reported diarrhea or vomiting 6 months after COVID‐19. 38 Sustained new bowel control problems were reported after COVID‐19 in 3 out of 100 hospitalized patients in a UK‐based study.…”
Section: Discussionmentioning
confidence: 99%
“… 9 , 10 , 11 , 12 , 13 Moreover, it appears that GI symptoms and sequelae are common after resolution of the acute COVID‐19 illness. 14 , 15 It has been proposed that these sustained symptoms fulfill a specific GI diagnosis, namely Disorders of Gut–Brain Interaction (DGBI), 16 which has been also explored in a recent study. 17 …”
Section: Introductionmentioning
confidence: 99%
“…They discovered that diarrhea, nausea/vomiting and abdominal pain were the most common GI symptoms the admission time. Nevertheless, after a median following up of 106 days, abdominal pain (7.5%) was the most frequent symptom followed by constipation, diarrhea and vomiting [ 31 ]. Hereby, Gastrointestinal sequelae stood for 93/249 (37.3%) cases in which abdominal pain was dominant following by nausea and difficulty in swallowing in both acute and the persistent states.…”
Section: Discussionmentioning
confidence: 99%